The Relationship between Students' Misconception Levels Using Four Tier Diagnostic Tests with Concept Understanding - Agus Budiyono; Milisa Triastutik; Arin Wildani (STAI Hubbulwathan Duri, 2022)
This study was conducted to know the relationship between the level of students' misconceptions and students' understanding. This study uses a quantitative descriptive method with a correlative research model. This research was conducted in MA. Miftahul Ulum Bettet Pamekasan in February 2022. The population in this study were all class X students with samples of class X Mathematics and Natural Sciences A, B, and C taken using the purposive sampling method. Data on the level of student misconceptions was obtained using a four-tier diagnostic test and analyzed with student understanding data using SPSS 25. The data obtained in the study, namely the correlation coefficient value was obtained at 0.088, which means that the level of relationship between students' understanding variables and students' level of misconceptions variables is very weak.